Effects of chromium picolinate on the viability of chick embryo fibroblast. (April 2014) - Bai, Y; Zhao, X; Qi, C; Wang, L; Cheng, Z; Liu, M; Liu, J; Yang, D; Wang, S; Chai, T
Chromium picolinate (CrPic), which is used as a nutritional supplement and to treat type 2 diabetes, has gained much attention because of its cytotoxicity. This study evaluated the effects of CrPic on the viability of the chick embryo fibroblast (CEF) using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide assay, morphological detection, and flow cytometry. The results show that lower concentrations of CrPic (8 and 16 μM) did not damage CEF viability ( p > 0.05). However, higher CrPic concentrations (400 and 600 μM) indicated a highly significant effect on the production of intracellular reactive oxygen species, alteration of mitochondrial membrane potential, intracellular calcium ion concentration, and the apoptosis rate ( p < 0.01), contrary to lower CrPic concentrations (8 and 16 μM) and control group. Moreover, apoptotic morphological changes induced by these processes in CEF were confirmed using Hoechst 33258 staining. Cell death induced by higher concentrations of CrPic was caused by an apoptotic and a necrotic mechanism, whereas the main mechanism of oxidative stress-induced mitochondrial dysfunction was apoptotic death.